STRUKTUR CERITA DALAM CERPEN “KUCINGKU SAYANG” KARYA WERDININGSIH: ANALISIS UNSUR INTRINSIK - Maura Jesa Vianny; Rosalia; Ajeng Pramudyasari; Margareta Nofi Kristi; Saptiana Sulastri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study analyzes the intrinsic elements in the short story “Kucingku Sayang” written by Werdiningsih. The problem of this research is how the intrinsic elements build the structure of the story. The purpose of this study is to describe the intrinsic elements contained in the short story, including theme, characters and characterizations, plot, setting, point of view, language style, and moral message. This research uses a descriptive qualitative method. The data source is the short story “Kucingku Sayang” which is included in a collection of children's short stories. Data were collected through literature study by reading, understanding, and recording parts of the story related to intrinsic elements. The data were analyzed through the stages of identification, classification, description, and interpretation. The results show that the theme of the story is affection and responsibility toward pets. The main character, Tya, is portrayed as a caring child who loves her pet cat named Momo. The story uses a progressive plot with simple language and a first-person point of view. The moral message emphasizes empathy, responsibility, and affection toward living beings.